FlexFacs: An online training and educational resource for OMFS specialty trainees. Issue 1 (January 2022) - Nugent, Michael; Garg, Montey; Bentley, Robert
Abstract : Introduction: Whilst there are a number of online training resources available, as yet none are mapped to the OMFS curriculum. A pilot virtual national teaching for OMFS specialty trainees (STs) during COVID received very positive feedback from STs last year. There is an unmet need for a systematic OMFS online learning resource for OMFS STs. BAOMS 2020 President Mr Rob Bentley has used part of his Presidential Fund to set up and support this online education programme in direct response to the shift to online learning. Methods: The programme will deliver monthly live lectures, with content mapped to the OMFS curriculum. These lectures will then be made available for access online permanently. Over a three-year period, the lectures will cover the syllabus. Additionally, how to do it videos will be added to FlexFacs. Quizzes and games based around the recorded lectures will be made available also. There are plans to make 'virtual reality' surgery content available for trainees along with an indexed repository of webinar lectures on the FlexFacs website. Results: Feedback received from OMFS STs was very positive. 98 percent of the OMFS STs who attended the pilot webinars rated it as 'excellent' or 'very good' and 99 percent found the content 'extremely useful' or 'very useful'. The inaugural lecture was delivered on 21st September 2021. Conclusions: FlexFacs is the innovative, brand-new online training and educational resource for OMFS STs launched by the BAOMS. We encourage all OMFS trainees, trainers and training programme directors to engage with FlexFacs.